Analysis of M.Quraish Shihab's Preaching Message "in the Study of Liver Disease" on Najwa Shihab's Youtube Channel - Nurul Ummah (INJECT (Interdisciplinary Journal of Communication), 2024)
This study examines the message of M. Quraish Shihab's da'wah in studying liver disease on Najwa Shihab's YouTube channel. The focus of the problem in this article's research is what messages are in the study and which messages are more dominant in the study of liver disease delivered by M. Quraish Shihab. This study aims to find out what messages are contained in the study of liver disease. This study uses the descriptive content analysis method by analyzing the dialogue text in the liver disease study video. The data collection technique in this study is observation, namely by observing the video of the study of liver disease by M. Quraish Shihab on Najwa Shihab's YouTube channel. As primary data, the researcher will transcribe the video of the study of liver disease, which is divided into three parts. For secondary data, the researcher will write the da'wah messages from M. Quraish Shihab in the Study of Liver Disease on Najwa Shihab's YouTube channel. The study of liver disease contains three categories of da'wah messages: morals, aqidah, and sharia. The video's results on the liver disease study delivered by M. Quraish Shihab contained 25 messages. The results of the moral preaching messages were 13, the faith preaching messages were 10, and the sharia preaching messages were 2, so in this study of heart disease, moral messages dominated.